Cumulative Environmental Impact of Humans’ (Agro-Busines) Activities - Jeffrey Warner; Fajar Rizki Widiatmoko; Tsai-Ping Wang (Journal of Earth and Marine Technology (JEMT), 2022)
This study analyzed the wastewater discharge of a four-region area comprised of agro-businesses (i.e. vegetable as well as commercial animal farms) and an adjacent urban area. Each region is respectively using a five-kilometer-long human-made irrigation system that collectively concludes at (and is injecting wastewater into) a major river leading to the Pacific Ocean. Using research methodology involving scientific measurements taken at strategic points located throughout this irrigation system, we deductively isolated which region in this overall area is the most significant respective contributor to the amassed wastewater. We hypothesized that the agro-business area involving commercial animal farming would be the most significant contributor. While we discovered that this is partly correct, the urban area is discharging the most concentrated levels of waste, including raw sewage.We do suspect that Taiwan’s environmental pollution regulations are beingviolated.However, further analysis involving wastewater volume, soil analysis, agro-business, and urban social construction identification, as well as the identifying of relevant environmental protection laws is still needed. This would best capacitate activism efforts toward lobbying government ornon-government organizations for potential environmental violations related to the intervention.